Perspectives on biological growth and remodeling. - Ambrosi, D; Ateshian, G; Arruda, E; Cowin, S; Dumais, J; Goriely, A; Holzapfel, G; Humphrey, J; Kemkemer, R; Kuhl, E; Olberding, J; Taber, L; et al. (2011)
The continuum mechanical treatment of biological growth and remodeling has attracted considerable attention over the past fifteen years. Many aspects of these problems are now well-understood, yet there remain areas in need of significant development from the standpoint of experiments, theory, and computation. In this perspective paper we review the state of the field and highlight open questions, challenges, and avenues for further development.